AMAP score prediction of hepatocellular carcinoma occurrence and incidence‐free rate after a sustained virologic response in chronic hepatitis C. Issue 9 (12th July 2021) - Yamashita, Yuki; Joshita, Satoru; Sugiura, Ayumi; Yamazaki, Tomoo; Kobayashi, Hiroyuki; Wakabayashi, Shun‐ichi; Yamada, Yosuke; Shibata, Soichiro; Kunimoto, Hideo; Iwadare, Takanobu; Matsumura, Makiko; Miyabayashi, Chiharu; et al.
Abstract: Aims: Hepatocellular carcinoma (HCC) can still occur in hepatitis C virus (HCV) patients who have achieved a sustained virologic response (SVR), which remains an important clinical issue in the direct‐acting antivirals era. The current study investigated the clinical utility of the aMAP score (consisting of age, male, albumin–bilirubin, and platelets) for predicting HCC occurrence in HCV patients achieving an SVR by direct‐acting antivirals. Methods: A total of 1113 HCV patients without HCC history, all of whom achieved an SVR, were enrolled for clinical comparisons. Results: Hepatocellular carcinoma was recorded in 50 patients during a median follow‐up period of 3.7 years. The aMAP score was significantly higher in the HCC occurrence group than in the HCC‐free group (53 vs. 47, p  < 0.001). According to risk stratification based on aMAP score, the cumulative incidence of HCC occurrence for the low‐, medium‐, and high‐risk groups was 0.14%, 4.49%, and 9.89%, respectively, at 1 year and 1.56%, 6.87%, and 16.17%, respectively, at 3 years (low vs. medium, low vs. high, and medium vs. high: all p  < 0.01). Cox proportional hazard analysis confirmed aMAP ≥ 50 (hazard ratio [HR]: 2.78, p = 0.014), age≥ 70 years (HR: 2.41, p = 0.028), ALT ≥ 17 U/L (HR: 2.14, p < 0.001), and AFP ≥ 10 ng/mL (HR: 2.89, p = 0.005) as independent risk factors of HCC occurrence. Interestingly, all but one patient (99.5%) with aMAP less than 40 was HCC‐free following an SVR. Conclusion: The aMAP score could have clinical utility for predicting HCC occurrence in HCV patients achieving an SVR.